2002
DOI: 10.4049/jimmunol.168.4.1911
|View full text |Cite
|
Sign up to set email alerts
|

Eotaxin-2 Generation Is Differentially Regulated by Lipopolysaccharide and IL-4 in Monocytes and Macrophages

Abstract: The eotaxins are a family of CC chemokines that coordinate the recruitment of inflammatory cells, in particular eosinophils, to sites of allergic inflammation. The cDNA for eotaxin-2 (CC chemokine ligand 24) was originally isolated from an activated monocyte library. In this study, we show for the first time that peripheral blood monocytes generate bioactive eotaxin-2 protein constitutively. Eotaxin-2 production was significantly up-regulated when monocytes were stimulated with the proinflammatory cytokine IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 64 publications
5
57
1
Order By: Relevance
“…Moreover, MMP-9 and eotaxin-2 were decreased in the peritoneal cavity of Thy-1 À/À mice upon induction of inflammation by thioglycollate. As shown by other groups, we also detected these products in granulocytes or monocytes by RT-PCR [33][34][35][36][37]. Thus, the decreased number of granulocytes and macrophages in Thy-1 À/À mice might be directly responsible for the reduced levels of these cytokines, chemokines, and protease in the BAL or peritoneal fluid of Thy-1 À/À mice.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, MMP-9 and eotaxin-2 were decreased in the peritoneal cavity of Thy-1 À/À mice upon induction of inflammation by thioglycollate. As shown by other groups, we also detected these products in granulocytes or monocytes by RT-PCR [33][34][35][36][37]. Thus, the decreased number of granulocytes and macrophages in Thy-1 À/À mice might be directly responsible for the reduced levels of these cytokines, chemokines, and protease in the BAL or peritoneal fluid of Thy-1 À/À mice.…”
Section: Discussionsupporting
confidence: 78%
“…Data from Furusho et al, describing an association of the number of eosinophils and the level of IL-4 and IL-5 concentrations in BAL in an murine model of toluene diisocyanate-induced asthma [32], support our findings. Our own PCR data and Watanabe et al show that peripheral monocytes generate eotaxin-2 constitutively [35]. Furthermore, IL-4 augmented eotaxin-2 expression in allergic lung inflammation [38].…”
Section: Discussionsupporting
confidence: 65%
“…Second, eotaxin-1 is known to be involved in the early phase (6-24 h) of allergic inflammation (37)(38)(39)(40), and our protocol (sacrifice 24 or 48 h after the final challenge) may have failed to evaluate ALN's effect on the production of eotaxin-1 in the lung. According to previous in vitro reports, eotaxin-1 production is limited to airway smooth muscle cells, epithelial cells, and fibroblasts (43,50,51). We could not detect eotaxin-1 from pleural macrophages under any conditions (with LPS and/or IL-4, -17, -33) in vitro (data not shown); therefore, we could not fully confirm ALN's effect on the production of eotaxin-1 by macrophages.…”
Section: Discussioncontrasting
confidence: 50%
“…Eotaxin-1-deficient mice are able to develop airway eosinophilia and airway hyperresponsiveness in a model of experimental asthma [19,20], implying that other eosinophil-active chemoattractants are also involved in eosinophil recruitment into the airways. Th2 cytokines differentially regulate eotaxin-2 expression in monocytes and macrophages [21]. Recent studies of eotaxin-2-deficient mice have revealed an eotaxin-2-dependent mechanism in IL-13-induced airway eosinophilia [22].…”
Section: Introductionmentioning
confidence: 99%